Narratives of German History After the Reformation - Dixon, C. Scott (The historical journal, 1998)
Die katholische Konfessionalisierung. Edited by Wolfgang Reinhard and Heinz Schilling. ‘Schriften des Vereins für Reformationsgeschichte’, Vol. 198. Gütersloh: Gütersloher Verlagshaus, 1995. Pp. xiii+472. ISBN 3-579-01666-0. DM 148.The Salzburg transaction: expulsion and redemption in eighteenth-century Germany. By Mack Walker. Ithaca and London: Cornell University Press, 1992. Pp. xvi+242. ISBN 0-8014-2777-0. USD38.50.War, state and society in Württemberg, 1677–1793. By Peter H. Wilson. Cambridge: Cambridge University Press, 1995. Pp. xvii+294. ISBN 0-521-47302-0. £18.95.Kaiser Maximilian II. Kultur und Politik im 16. Jahrhundert. Edited by Friedrich Edelmayer and Alfred Kohler. ‘Wiener Beiträge zur Geschichte der Neuzeit’, Vol. 19. Munich: R. Oldenbourg Verlag, 1992. Pp. 263. ISBN 3-486-0317-3. ÖS 396.Post-Reformation development in Germany has few of the features that encourage historians to describe an age with a catchy noun or turn of phrase. As a land comprised of hundreds of principalities, dioceses, and free imperial cities, Germany does not easily lend itself to descriptions of the evolving state. Equally, as the German lands were divided by confessional alliance and subject to a wide range of intellectual currents and traditions, it has proven difficult to come up with a term comprehensive enough to include the full sweep of social, religious, and intellectual life. Most of the concepts we use to define European development in this age fall short when applied to Germany. In view of this, historians tend either to emphasize certain aspects of the nation's development, or to isolate events that seem to reveal something central. Both approaches have been taken in the books under review.